2015
DOI: 10.1002/hep.27677
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor–induced lysine‐specific histone demethylase reduces hepatic bile acid levels and protects the liver against bile acid toxicity

Abstract: Bile acids (BAs) function as endocrine signaling molecules that activate multiple nuclear and membrane receptor signaling pathways to control fed-state metabolism. Since the detergent-like property of BAs causes liver damage at high concentrations, hepatic BA levels must be tightly regulated. BA homeostasis is regulated largely at the level of transcription by nuclear receptors, particularly the primary bile acid receptor, farnesoid X receptor (FXR), and small heterodimer partner (SHP) that inhibits BA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 34 publications
(98 reference statements)
2
46
0
Order By: Relevance
“…The current study reveals multiple transcriptionally regulated pathways that are initiated after feeding by the bile acid nuclear receptor FXR and further demonstrate the link between bile acid signaling and the autophagic pathway. Upon food intake, bile acid‐activated FXR directly represses hepatic autophagy genes (Lee et al , ; Seok et al , ), but also induces the expression of SHP, LSD1 (Kim et al , ), and FGF15/19 (Inagaki et al , ). Thus, direct FXR repression of autophagy would be expected to precede that by FXR‐induced SHP, LSD1, and FGF15/19.…”
Section: Discussionmentioning
confidence: 99%
“…The current study reveals multiple transcriptionally regulated pathways that are initiated after feeding by the bile acid nuclear receptor FXR and further demonstrate the link between bile acid signaling and the autophagic pathway. Upon food intake, bile acid‐activated FXR directly represses hepatic autophagy genes (Lee et al , ; Seok et al , ), but also induces the expression of SHP, LSD1 (Kim et al , ), and FGF15/19 (Inagaki et al , ). Thus, direct FXR repression of autophagy would be expected to precede that by FXR‐induced SHP, LSD1, and FGF15/19.…”
Section: Discussionmentioning
confidence: 99%
“…3 First, they discovered functional FXR binding motifs, inverted repeat element 1, in the intron regions of the Lsd1 gene. 2 They also found that pharmacological or physiological activation of FXR signaling induced expression of Lsd1 in mouse liver. Farnesoid X receptor-induced Lsd1 directly interacted with SHP and enhanced gene repression by SHP in reporter assays.…”
mentioning
confidence: 97%
“…In the current issue of HEPATOLOGY, Kim et al add to the complexity of SHP-mediated transcriptional repression involved in fine-tuning of bile acid homeostasis by linking demethylation of a histone activation mark with FXR-dependent gene repression through the induction of SHP. 2 They showed convincingly that FXR induces, with the help of SHP, the expression and recruitment of the lysine-specific histone demethylase LSD1 to the CYP7a1 and CYP8b1 loci, leading to epigenetic repres-sion of bile synthesis. Lysine (K)-specific demethylase 1 (LSD1) is a histone demethylase that demethylates both lysine 4 (H3K4me) and lysine 9 (H3K9me) of histone H3 NH 2 -terminal tails, potentially acting as a coactivator or a corepressor, depending on the cellular context.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SHP does not have a DNA binding domain but acts as a corepressor for numerous transcriptional factors . SHP links elevated hepatic BA levels to epigenetic repression of genes involved in BA synthesis and reuptake, including cholesterol 7α hydroxylase ( Cyp7a1 ), sterol 12α hydroxylase ( Cyp8b1 ), and sodium/taurocholate cotransporting polypeptide ( Ntcp ), by recruiting repressive histone‐modifying proteins to these genes . The gene regulatory functions and protein stability of SHP are enhanced by a late fed‐state intestinal hormone, fibroblast growth factor‐19 (FGF19, mouse FGF15) .…”
mentioning
confidence: 99%